Australian local government policies on creating a healthy, sustainable, and equitable food system: analysis in New South Wales and Victoria. (18th April 2022) - Carrad, Amy; Aguirre‐Bielschowsky, Ikerne; Reeve, Belinda; Rose, Nick; Charlton, Karen
Abstract: Objective : To analyse local government (LG) policies concerned with creating a healthy, sustainable and equitable food system. Methods : All relevant policies on LG websites were identified and analysed against a framework of 34 recommendations for LG action on food system issues. Results : A total of 13 of 207 (New South Wales 128, Victoria 79) LGs had dedicated food system policies. Most actions on food system issues were in general (non‐food specific) policies. Most LGs acted on food safety, sustainable local food production, food waste, drinking water access and food system‐related education. Few used economic measures to support the consumption of healthier foods, restricted unhealthy food advertising, developed and implemented dietary guidelines in LG‐managed settings or influenced the opening of unhealthy/healthy retail food outlets. Conclusions : LGs undertook a range of actions relevant to creating a healthy, sustainable and equitable food system. Strategic opportunities for LGs include regulating the sale and marketing of unhealthy food and ensuring policy coherence. Implications for public health : LGs can be supported to act further on food system issues, including through 'joined‐up' state and federal policies. Further research should address how relevant LG policies can be developed, implemented and monitored effectively to address the complex challenges created by contemporary food systems.